Antifungal activity of gum-resin extracts of Boswellia serrata, Commiphora mukul, Gardenia resinifera and Shorea robusta against some plant pathogenic fungi - UJWALA C. BAPAT, SMITA HENRY GAUREA*, SMRITY PRABHA and (Indian Phytopathology, 2017)
Resins are formed as oxidation products of various essential oils and are very complex and varied in chemical composition. They are usually secreted in definite cavities or passages. They frequently ooze out through the bark and harden on exposure to air.Resin production is widespread in nature and is reported from plants of Pinaceae, Araucariaceae, Umbelliferae, Dipterocarpaceae, Burseraceae, Rubiaceae and Sterculiaceae. Ethanolic extracts of gum resins of Boswellia serrata, Commiphora mukul, Gardenia resinifera and Shorea robusta were screened for their antifungal activity in vitro against phytopathogenic fungi, Aspergillus niger Tiegh., Fusarium oxysporum Schlecht., Nigrospora oryzae (Berk and Br.) Petch., Rhizoctonia solani J.G.Kuhn., and Sclerotium rolfsii Sacc and rot fungus Rhizopus stolonifer (Ehrenb.: Fr.) Vuill. The antifungal activity was tested by poisoned food technique. The results obtained showed that the growth of fungi, Rhizoctonia solani and S. rolfsii, was stimulated by all the resin extracts. Extracts of B. serrata and S. robusta caused no inhibition of mycelial growth of the fungi tested. It was observed that the resin extract of G. resinifera was the most effective against N. oryzae and showed 77.16% inhibition of mycelia growth of N. oryzae at the concentration of 111mg/ml.